Oxidative aging of epoxy asphalt. Issue 5 (16th April 2022) - Apostolidis, Panos; Liu, Xueyan; Erkens, Sandra; Scarpas, Tom
ABSTRACT: Oxidative aging is responsible for the irreversible asphalt stiffening and embrittlement leading to asphalt pavements of increased susceptibility to fatigue and thermal cracking. In recent years, various flexible binders have been introduced in asphalt industry to produce long-life pavements and the epoxy asphalt binders are among them. Nevertheless, in-depth understanding of the oxidative aging mechanism of epoxy asphalt binders and binding systems is still needed to enable reliable predictions of material degradation through service life. In this research, the compositional and rheological changes of epoxy asphalt, with and without filler, were analysed by means of Fourier Transform Infrared spectroscopy and Dynamic Shear Rheometer. Especially, kinetics (Arrhenius) parameters of epoxy asphalt have been determined by tracking the chemical composition changes. Oxidation of carbon species in epoxy asphalt is compositional dependent, and low values of activation energy accompany in low values of reaction rate are shown by adding epoxy in asphalt. Furthermore, the epoxy asphalt mastics (binders with filler) have been subjected to rheological testing to evaluate the stiffening effect as oxidation proceeds. Increase of modulus over a wide range of frequencies, decrease of frequency dependency of modulus of epoxy asphalt and shifting of phase angle to lower values are some important observations noticed as well. Overall, oxidation in epoxy asphalt materials occurs slowly yielding to oxygen-resistant binders when epoxy compounds are incorporated in asphalt binders.